Ddx20, DEAD box helicase 20, is essential for the differentiation of oligodendrocyte and maintenance of myelin gene expression. Issue 11 (7th July 2021) - Simankova, Anna; Bizen, Norihisa; Saitoh, Sei; Shibata, Shinsuke; Ohno, Nobuhiko; Abe, Manabu; Sakimura, Kenji; Takebayashi, Hirohide
Abstract: Oligodendrocytes form myelin sheaths that surround axons, contributing to saltatory conduction and proper central nervous system (CNS) function. Oligodendrocyte progenitor cells (OPCs) are generated during the embryonic stage and differentiate into myelinating oligodendrocytes postnatally. Ddx20 is a multifunctional, DEAD‐box helicase involved in multiple cellular processes, including transcription, splicing, microRNA biogenesis, and translation. Although defects in each of these processes result in abnormal oligodendrocyte differentiation and myelination, the involvement of Ddx20 in oligodendrocyte terminal differentiation remains unknown. To address this question, we used Mbp‐Cre mice to generate Ddx20 conditional knockout (cKO) mice to allow for the deletion of Ddx20 from mature oligodendrocytes. Mbp‐Cre;Ddx20 cKO mice demonstrated small body sizes, behavioral abnormalities, muscle weakness, and short lifespans, with mortality by the age of 2 months old. Histological analyses demonstrated significant reductions in the number of mature oligodendrocytes and drastic reductions in the expression levels of myelin‐associated mRNAs, such as Mbp and Plp at postnatal day 42. The number of OPCs did not change. A thin myelin layer was observed for large‐diameter axons in Ddx20 cKO mice, based on electron microscopic analysis. A bromodeoxyuridine (BrdU) labeling experiment demonstrated that terminal differentiation was perturbed from ages 2 weeks to 7 weeks in the CNS of Mbp‐Cre;Ddx20 cKO mice. The activation of mitogen‐activated protein (MAP) kinase, which promotes myelination, was downregulated in the Ddx20 cKO mice based on immunohistochemical detection. These results indicate that Ddx20 is an essential factor for terminal differentiation of oligodendrocytes and maintenance of myelin gene expression. Main Points: Oligodendrocyte differentiation and maintenance of myelin gene expression are disturbed by Ddx20 deletion in oligodendrocytes. Dysregulation of myelin gene splicing and reduced MAPK activation are observed in spinal cords of the Ddx20 cKO mice.